Comparison of effects of different teaching modes in medical imaging teaching - Han Qinghe; Gong Tingting; Meng Yuan; Cao Qian; Liu Jianhua (Guoji laonian yixue zazhi)
[Objective] To investigate the efficacy of traditional teaching methods, “live online+self-study,” and blended teaching methods in undergraduate medical imaging education. [Methods] A retrospective analysis method was employed to categorize 5-year clinical medicine students, who were enrolled in the medical imaging theory course at the Second Hospital of Jilin University from March 2019 to March 2021, into three distinct groups. Group A consists of 66 students of 2016 grade who were taught by traditional teaching methods. Group B comprises 72 students of 2017 grade who were taught by a combination of live onlive and self-study. Group C consists of 69 students in 2018 grade who were taught by a blended teaching approach that combines both online and offline methods. The efficacy of instruction is assessed by the analysis of examination outcomes. [Results] The final scores of the three groups，Group B achieved a higher score compared to both Group A and Group C, with a statistically significant difference (P<0.01). However, there was no statistically significant difference between Group A and Group C(P>0.05). [Conclusion] The instructional approach of “live online+self-study” ensures the quality of the class and the effectiveness of teaching.